Inhaled corticosteroids and beta2-agonists - Usmani, Omar S. (Henry Stewart Talks, 2012)
Asthma treatment guidelines, Pharmacology of inhaled corticosteroids and long-acting beta agonists, Clinical evidence for combination therapy in asthma, Molecular interactions between inhaled corticosteroids and long-acting beta agonists